Interest rates and implications for microfinance in Latin America and the Caribbean - Anita Campion; Rashmi Kiran Ekka; Mark Wenner (Inter-American Development Bank (IDB), 2010)
Microfinance institutions (MFIs) have been successful in providing credit to millions of low-income borrowers in groups previously excluded from formal financial services, but they often charge interest rates that many claim are excessive. We examine microfinance interest rates and their determinants in order to understand how these rates might be lowered. Using high-quality financial data from 29 institutions in seven countries over a period of four years, and drawing on information from field visits with clients, we explore patterns of cost and efficiency in MFIs. We find that improved operational efficiency comes with increased competition and institutional age, or learning by doing. Encouragingly, our regression analysis shows patterns of profit-making MFIs charging lower interest rates. We also find that interest rate caps reduce the outreach of these institutions to the poor, women, and rural clients.
hdl:11319/4298
Keywords: G21; O16; E43; 330; interest rates; efficiency; microfinance